2013
DOI: 10.1080/01411926.2012.659720
|View full text |Cite
|
Sign up to set email alerts
|

‘Take more time to actually listen’: students' reflections on participation and negotiation in school

Abstract: Behaviour in schools is an emotive topic and one of enduring political interest and sensitivity. The media often portrays schools as violent and dangerous places and young people as ever more unruly. This paper explores findings from a recent large‐scale national study on behaviour and focuses on the data from primary and secondary school students within this study. The comments and suggestions offered by students move beyond a discussion of behaviour to focus on the broader questions of participation, engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
0
25
0
4
Order By: Relevance
“…A similar connection between a fair investigation of disciplinary events and children's voice has been reported in other studies exploring children's perceptions of school discipline (Osler, ; Bracy, ; McCluskey et al ., ). Children's rights to participation in decisions that affect them, and to be heard in administrative proceedings, are anchored in Article 12 of the UNCRC and are interconnected with many other rights (see Lundy, ; Perry‐Hazan, ; Gal, ; Tisdall, ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A similar connection between a fair investigation of disciplinary events and children's voice has been reported in other studies exploring children's perceptions of school discipline (Osler, ; Bracy, ; McCluskey et al ., ). Children's rights to participation in decisions that affect them, and to be heard in administrative proceedings, are anchored in Article 12 of the UNCRC and are interconnected with many other rights (see Lundy, ; Perry‐Hazan, ; Gal, ; Tisdall, ).…”
Section: Discussionmentioning
confidence: 97%
“…Pupils also raised concerns with regard to their voice and participation in school discipline. They complained that educators do not listen to them sensitively enough to understand the events under discussion (McCluskey et al ., ), and that their minds are made up before they hear the pupil's perspective (Bracy, ). Similarly, Raby () found that pupils had only little expectation that they would be able to influence school rules beyond the basic parameters of following or breaking the rules.…”
Section: Pupils’ Perceptions Of School Disciplinementioning
confidence: 99%
See 3 more Smart Citations